Sentiment Analysis of Indonesian Presidential Candidate Before and After the Election - Sofyan, Muhammad Hilmy Rasyad; Zulkifli, Akmal; Rasim, Rasim (Universitas Multimedia Nusantara, 2024)
As one of the world's democratic countries, Indonesia has just held a general election to choose its next president. The development of the times encourages presidential candidates to make a new breakthrough, such as the use of social media as campaign media. Currently, X is a popular social media used as a campaign medium. On X, users are given the freedom to share their opinions. Various opinions related to one of the presidential candidates were used by the researchers to collect data using the data crawling method. The results of the data crawling are first processed with different methods in the pre-process to make the data ready for use. Some of the steps that need to be taken in the pre-process are such as cleaning, normalisation, stopword, tokenisation, stemming and translation processes. All the processes carried out in the pre-process stage will produce mature or usable data. The mature data is then classified into positive, negative and neutral using the Naïve Bayes classification method. Once the classification is complete, the results are evaluated in terms of sentiment towards one of the presidential candidates. The results of a total of 2117 data collected from 01 February 2024 to 20 May 2024, there are 390 data used for the pre-presidential election sentiment analysis and 1618 data used for the post-presidential election sentiment analysis. Both before and after the presidential election was held, this presidential candidate had more positive sentiments than the negative and neutral sentiments he received from the public.